Gambaran Program Kesehatan pada Dinas Pencegah Pemadam Kebakaran di Kota Medan - Afifah, Adinda; Rifdah, Annisa Aisy; Ansari, Cindi; Derina, Derina; Herawaty, Desy; Amira, Farah; Nabila, Febri; Utari, Luthfiyah; Shafa, Natasya; Rahmalila, Nindy; Nurwana, Rena ; Aulia, Tasya; Chaniago, Tessya; Hastuty, Widya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Medan City Fire Prevention Service or often abbreviated as Damkar or PMK is an institution consisting of people pf troops tasked with extinguishing fires, conducting rescues, and dealing with disasters or other incidents. The Medan City Fire Departement is one of the agencies that prioritizes the work safety of its employees. The purpose of this paper is to analyze the description of the health program implemented at the Fire Prevention Service in Medan City. This Study uses qualitative methods in the form of primary and secondary data. The number of informants is 1 person. The results of this study found that before the Covid-19 pandemic there were several health programs implemented at the Fire Prevention Service. The conclusion from this study is that there are still several obstacles related to the health program that is implemented. Keyword: Health Programs, Fire Fighter